Understanding dual realities and more in VR. (31st May 2018) - Pan, Xueni; Hamilton, Antonia F. de C.
Abstract : The five commentaries on our paper (Pan & Hamilton, 2018, Br. J. Psychol .) provide a useful summary of the key issues we raise, and also bring to the foreground some new and important questions, touching on a range of issues including presence and the conceptualization of dual realities. We highlight here some important themes and directions for future investigation.